Hydraulic properties of well screens - Corey, Gilbert L., author; Lewis, Robert L., advisor; Rohwer, Carl, committee member (Colorado State University. Libraries, 1949)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Wells